Main findings of the Global Comparative Study on Tenure in Uganda - Mwangi, E. (2020)
Since the adoption of the 2003 National Forestry and Tree Planting Act (NFTPA) in Uganda, there have been only a few assessments of how forest tenure reform is progressing. Here we present the key findings of research undertaken as part of the Global Comparative Study (GSC) on Forest Tenure Reform in Uganda, which complements the work that has been done by generating lessons and insights for policy and practice.